Evaluating optical coherence tomography for surgical margin assessment of canine mammary tumours. (26th July 2020) - Fabelo, Carolina; Selmic, Laura E.; Huang, Pin‐Cheh; Samuelson, Jonathan P.; Reagan, Jennifer K.; Kalamaras, Alexandra; Wavreille, Vincent; Monroy, Guillermo L.; Marjanovic, Marina; Boppart, Stephen A.
Abstract: Optical coherence tomography (OCT) uses near‐infrared light waves to generate real‐time, high‐resolution images on the microscopic scale similar to low power histopathology. Previous studies have demonstrated the use of OCT for real‐time surgical margin assessment for human breast cancer. The use of OCT for canine mammary tumours (CMT) could allow intra‐operative visualisation of residual tumour at the surgical margins. The purpose of this study was to assess OCT imaging for the detection of incomplete tumour resection following CMT surgery. We hypothesized that the OCT images would have comparable features to histopathological images of tissues at the surgical margins of CMT resections along with a high sensitivity of OCT detection of incomplete surgical excision of CMT. Thirty surgical specimens were obtained from nineteen client‐owned dogs undergoing surgical resection of CMT. OCT image appearance and characteristics of adipose tissue, skin, mammary tissue and mammary tumour at the surgical margins were distinct and different. The OCT images of normal and abnormal tissues at the surgical margins were utilized to develop a dataset of OCT images for observer evaluation. The sensitivity and specificity for ex vivo images were 83.3% and 82.0% (observer 1) and 70.0% and 67.9% (observer 2). The sensitivity and specificity for in vivo images were 70.0% and 89.3% (observer 1) and 76.7% and 67.9% (observer 2). These results indicate a potential use of OCT for surgical margin assessment for CMT to optimize surgical intervention and clinical outcomes. Improved training and experience of observers may improve sensitivity and specificity.